The impact of product innovation on female entrepreneurship success: A case of Saudi Arabia - Shabir Ahmad (Agora International Journal of Economical Sciences (AIJES), 2024)
Recent reforms in Saudi Arabia granted empowerment to women, opening new entrepreneurial avenues for them. This study aims to assess the influence of product innovation on the success of female entrepreneurs in Saudi Arabia. Employing a quantitative approach, data was collected through a survey questionnaire. The primary data set included responses from 256 Saudi female entrepreneurs. SmartPLS was utilized for analysis, employing the PLS-SEM statistical technique. The results revealed a positive overall effect of product innovation on female entrepreneurs and their intentions. The study offers practical insights for female entrepreneurs and the Saudi government to address challenges faced by Saudi women. Recommendations include the formulation of policies that provide sustained support for women entrepreneurs. Additionally, the study suggests potential avenues for future research in this domain.
Keywords: 330